Elimination of the consequences of natural disasters - Imamaliyeva, J. (Ways to Improve Construction Efficiency, 2019)
In this work natural disasters which are the tragedy for all state, and, especially for those regions of the country where they arise are investigated. The correct behavior of the population at natural disasters relying on knowledge of bases of civil defense is a basis of decrease in human losses and material damage. In article it is noted that actions of the population at natural disasters and at elimination of their consequences have to carry out in strict accordance with instructions of bodies of civil defense